2022
DOI: 10.2174/1389201022666210719155931
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products and some Semi-synthetic Analogues as Potential TRPV1 Ligands for Attenuating Neuropathic Pain

Abstract: : Natural products and leads inspired by them have acted as a probe for successful drug discovery for many decades. Pain is an obnoxious sensory and emotional experience associated with potential tissue damage. It affects the quality of life of patients to a great extent. Despite the availability of several agents targeting TRP receptors, none of them can proficiently alleviate neuropathic pain. TRPV1 is a prospective target for treating neuropathic pain as it is recognized to modulate the pain circuitry at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Gaurav G-N et al recently showed that natural products and some semi-synthetic analogs as potential TRPV1 ligands for attenuating neuropathic pain. 25 Akhilesh et al reviewed Unlocking the potential of TRPV1 based siRNA therapeutics for the treatment of chemotherapy-induced neuropathic pain. 5 Pathogenic sensitization of TRPV1 is characterized by a decrease in the activation threshold and an increase in responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Gaurav G-N et al recently showed that natural products and some semi-synthetic analogs as potential TRPV1 ligands for attenuating neuropathic pain. 25 Akhilesh et al reviewed Unlocking the potential of TRPV1 based siRNA therapeutics for the treatment of chemotherapy-induced neuropathic pain. 5 Pathogenic sensitization of TRPV1 is characterized by a decrease in the activation threshold and an increase in responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Various plant-derived compounds such as capsaicin, curcumin, salicin and triptolide have been reported to provide pharmacotherapeutic activities against neuropathic pain. [12][13][14][15] These substances have preferred to synthetic drugs due to their less complication and fewer side effects as well as can confer several actions/effects concurrently such as anti-oxidant activity, anti-inflammatory, neuroprotective, modulation of pain management systems (opioids, serotonergic and cannabinoid systems) and ion channels. 15 Naringin, 4′,5,7-trihydroxyflavanone-7-rhamnoglucoside, is one of the main bioactive polyphenols derived from grape fruit and related citrus species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to oxidative stress, another feature of TRPV1 channels is that they can be activated by excessive temperature (T > 43°C) (Caterina et al, 1997; Naziroǧlu, 2012). It can also be activated by chemicals such as capsaicin, anandamide, resiniferatoxin and by environmental irritants such as camphor and allicin (Naik et al, 2022). The most effective antagonists on TRPV1 channels are capsazepine, 5′‐iodoreziniferatoxin, ruthenium red and various antioxidants (Wong & Gavva, 2009).…”
Section: Introductionmentioning
confidence: 99%